Literatura Norteamericana I: Template for Student Note-Taking - Bryla, Martyna Marika (My University, 2025)
This custom-made note-taking template was created to support students' learning in Literatura Norteamericana I, a required course in both the Degree in English Studies and the Double Degree in English Studies and Primary Education at the University of Málaga.
Keywords: Literatura norteamericana - Estudio y enseñanza; Literatura Norteamericana I; 19th century; Notes; Template